Neonatal rodent ventilation and clinical correlation in congenital diaphragmatic hernia. Issue 7 (5th May 2022) - Gupta, Vikas S.; Wilson, Cory; Popp, Elizabeth C.; Zhaorigetu, Siqin; Collum, Scott; Jin, Di; Khan, Amir M.; Karmouty‐Quintana, Harry; Lally, Kevin P.; Harting, Matthew T.
Abstract: Introduction: Ventilator management is a critical part of managing congenital diaphragmatic hernia (CDH). We aimed to use a murine model and patient data to study CDH‐associated differences in oxygenation, airway resistance, and pulmonary mechanics by disease severity. Methods: We used the nitrofen model of CDH. For control and CDH rodents, data were collected within the first hour of life. Oxygen saturations (SpO2 ) were collected using MouseOx, and large airway resistance and inspiratory capacities were collected using flexiVent. A single‐center, retrospective review of term CDH infants from 2014 to 2020 was performed. Tidal volumes were collected every 6 h for the first 48 h of life or until the patient was taken off conventional ventilation. Newborns that were mechanically ventilated but had no pulmonary pathology were used as controls. CDH severity was defined using the CDH Study Group (CDHSG) classification system. Results: Control rodents had a median SpO2 of 94% (IQR: 88%–98%); CDH pups had a median SpO2 of 27.9% (IQR: 22%–30%) ( p  < 0.01). CDH rodents had lower inspiratory capacity than controls (median: 110 μl, IQR: 70–170 vs. median: 267 μl, IQR: 216–352;  p  < 0.01). CDH infants had a lower initial SpO2 than control infants. Overall, CDH infants had lower tidal volumes than control infants (median: 4.2 ml/kg, IQR: 3.3–5.0 vs. 5.4 ml/kg, IQR: 4.7–6.2;  p  = 0.03). Tidal volumes varied by CDHSG stage. Conclusion: Newborns with CDH have lower SpO2 and lower, CDHSG stage specific, tidal volumes than control infants. The nitrofen model of CDH reflects these differences. Rodent models may be useful in studying therapeutic ventilatory strategies for CDH infants.